“Incidencia de recursos educativos digitales para el aprendizaje constructivista en la carrera pedagogía de ciencias experimentales informática, periodo octubre 2023 – marzo 2024.” - Romero Fernández, Juan Diego (2024)
In the current educational context, digital resources are indispensable due to their significant contribution to the teaching-learning process, which facilitates the development of meaningful understanding. The objective of the present research project is to evaluate the impact of digital educational resources. Accordingly, data mapping techniques are used to assess constructivist learning among students enrolled in the Online Experimental Sciences Pedagogy program during the period from October 2023 to March 2024. This research project employed various methods, including descriptive, explanatory, and correlational approaches. In addition, the study is conducted using a non-experimental design. Techniques such as deductions, documentary analysis, descriptive methods, inductive reasoning, and analytical-synthetic approaches are applied to facilitate the comprehensive analysis, representation, and interpretation of the information. Among these techniques, the survey method involved distributing a questionnaire to a sample of 166 students and 10 faculty members from the Experimental Sciences Pedagogy – Computer Science program to collect data. The research findings revealed the impact of digital educational resources on constructivist learning within the program. Specifically, when these resources are effectively integrated according to constructivist principles, they significantly improve the teaching and learning processes. The findings suggest that the use of digital educational resources and their perceived effectiveness in enhancing learning are viewed positively. However, while the teaching and learning processes in the Experimental Sciences Pedagogy program are based on the constructivist model, it is crucial to acknowledge that the implementation of this model is still lacking. The lack of previous research on this topic has been identified. Consequently, a pedagogical proposal has been developed, titled 'Didactic Guide for Pedagogical Intervention with Digital Educational Resources for Constructivist Teaching and Learning in the Experimental Sciences Pedagogy – Computer Science Program.' This proposal aims to provide detailed guidelines and pedagogical strategies for the effective integration of digital educational resources into the teaching-learning process, with the goal of promoting a constructivist approach. Keywords: Digital Educational Resources, DERs, Constructivist Learning, Computer Science Pedagogy.